2010
DOI: 10.1111/j.1741-3737.2010.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and the American Family: A Decade in Review

Abstract: Because of dramatic levels of economic volatility and massive changes in welfare policies, scholars in this decade worried anew about whether our official poverty measure, adopted in the 1960s, is adequate. Poverty's causes continued to be debated, with demographic factors often pitted against policy and maternal employment changes. Some scholars focused on events that trigger spirals into poverty or poverty exits. The literature on consequences of poverty featured new techniques for identifying underlying pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 136 publications
(154 reference statements)
2
65
0
Order By: Relevance
“…Beyond these examples, an extensive and deep literature concentrates on the individual risks of poverty (Cellini et al 2008;Dahl 2010;DiPrete 2002;Edin and Kissane 2010;Kohler et al 2012; McKeever and Wolfinger 2009;McLanahan 2004;Meyer and Wallace 2009;Ross et al 1987 from moral, cultural, or biological inadequacies -has dominated discussions of poverty for well over two hundred years and given us the enduring idea of the undeserving poor." Despite these occasional critiques however, there continues to be a great deal of scholarship on, discussion of, and interest in the risks of poverty.…”
mentioning
confidence: 99%
“…Beyond these examples, an extensive and deep literature concentrates on the individual risks of poverty (Cellini et al 2008;Dahl 2010;DiPrete 2002;Edin and Kissane 2010;Kohler et al 2012; McKeever and Wolfinger 2009;McLanahan 2004;Meyer and Wallace 2009;Ross et al 1987 from moral, cultural, or biological inadequacies -has dominated discussions of poverty for well over two hundred years and given us the enduring idea of the undeserving poor." Despite these occasional critiques however, there continues to be a great deal of scholarship on, discussion of, and interest in the risks of poverty.…”
mentioning
confidence: 99%
“…Poverty research in the United States has concluded that changes in employment status and earnings are more likely to lead to exits from poverty than changes in household structure and composition (Blank, 1997;Christopher, 2005;Lichter & Crowley, 2004;Lieb & Thistle, 2006;McKernan & Ratcliffe, 2005). Although changes in relationship status and the birth of children play a role in triggering entries into poverty, a recent review of the poverty literature's main findings concluded that changes in employment are more important in determining poverty status (Edin & Kissane, 2010). Moreover, in an intensive study of the culture and ideology of welfare offices, Hays (2003) noted that welfare caseworkers also tended to advocate work as a better strategy than marriage for escaping welfare and even expressed overt bias against encouraging women to rely on men's help.…”
Section: Routes Out Of Poverty Employmentmentioning
confidence: 99%
“…Overall, research on poverty has found that both household composition and changes in employment status and earnings are important for predicting poverty entries and exits, suggesting an interactive or cumulative effect of marriage and employment (Cancian & Danziger, 2009;Cellini et al, 2008;Edin & Kissane, 2010). At the same time, scholars have also argued that neither marriage nor employment offers a reliable escape from poverty for poor single mothers (Cancian, Haveman, Meyer, & Wolfe, 2002;Hays, 2003).…”
Section: Marriagementioning
confidence: 99%
“…In the US, several states have taken the initiative and added programs to provide partial lost income coverage for new parents under the Family and Medical Leave Act. Furthermore, child care subsidy programs in the US have proven to be a successful at reducing poverty and increasing work force participation (Edin and Kissane 2010).…”
Section: Implications and Recommendations For Policy Developmentmentioning
confidence: 99%